SIMULATION RESULTS OF COMPOSITED AND INTEGRATED AIRCRAFT FLIGHT ALTITUDE CONTROL SYSTEM - Kopytova, Kateryna (Proceedings of National Aviation University (archive), 2013)
The article deals with simulation results of the structure of flight altitude control system by means of elevator rudder controlling and integrated the structure of flight altitude control system by means of composited control over aerodynamic configuration of control surfaces.